Determination of the water content and D/H ratio of the martian mantle by unraveling degassing and crystallization effects in nakhlites. (1st December 2019) - Peslier, A.H.; Hervig, R.; Yang, S.; Humayun, M.; Barnes, J.J.; Irving, A.J.; Brandon, A.D.
Abstract: Knowing the distribution and origin of water in terrestrial planets is crucial to understand their formation, evolution and the source of their atmospheres and surface water. The nakhlites represent a suite of minimally shocked meteorites that likely originated from lava flows from a single volcano or from a shallow intrusion or sill complex on Mars. Measuring the water contents and D/H ratios of their igneous minerals allows identification of phases that have preserved their magmatic hydrogen, and therefrom permits estimation of the water content of their mantle source. Pyroxene, olivine, melt inclusions and mesostasis of five nakhlites (NWA 998, Nakhla, Y 000593, MIL 03346 and NWA 6148) were analyzed in situ for water contents and H isotopes, and major and trace element contents. No water was detected in olivine grains except in Y 000593. The water content of pyroxenes is highly heterogeneous within individual grains and between grains within a single meteorite. Water concentrations in pyroxene (<0.1–387 ppm H2 O), melt inclusions (26–4130 ppm H2 O) and mesostasis (1130–7850 ppm H2 O) decrease with increasing δD (from −268 to 4858‰) in all nakhlites. After ruling out significant influence from spallation, exchange with the martian atmosphere, shock, surface alteration, and hydrothermal processes, the H data of the pyroxenes can be explained by degassing and crystallization processes. Degassing is consistent with a decrease of water content from pyroxene interior to edge. Fractionation of H isotopes during degassing results in increases of δD during H loss from pyroxene but in decreases in δD during H2 O-OH loss from a melt. Consequently, the low-water content, high-δD of most pyroxenes is best explained by degassing after the pyroxenes had crystallized. All melt and plagioclase inclusions analyzed are located in degassed pyroxenes and are also degassed. The lower δD of the mesostasis (24 ± 131‰) compared to that of the least-degassed pyroxenes (430 ± 172‰) is likely the result of melt degassing and interaction with hydrothermal fluids. Magmatic H, however, has been preserved in each nakhlite in some pyroxenes that are characterized by >15 ppm H2 O and δD < 700‰. The H composition of the least-degassed, most-Mg-rich augites can be interpreted in two ways. If Cl-bearing hydrothermal fluids were assimilated by the parent magma of nakhlites prior to pyroxene crystallization, the H composition could represent a crustal signature. If hydrothermal fluid assimilation occurred after pyroxenes start crystallizing, it could be a mantle signature. We favor the latter scenario, in which case the martian mantle sampled by the nakhlites is estimated to contain 59–184 ppm H2 O and to have a δD of 430 ± 172‰. These water contents, similar to those of the upper part of the terrestrial mantle, represent those of a shallow depleted martian mantle reservoir. The two to four times higher δD of the martian mantle relative to that of Earth could have resulted from the two planets acquiring their water from different proportions and types of carbonaceous chondrite-like planetesimals.